From nationalization to regulation. Energy legislation in Poland 1945-1997 - Nowacki, Tomasz (Studia Iuridica Toruniensia, 2023)
This article is an attempt to concisely present the changes in Polish energy legislation that took place between the end of World War II in 1945 and the enactment of the Energy Law in 1997, i.e., over 50 years later. At that time, several most important chapters in the history of energy law can be distinguished: nationalization, change of the economic system including the power sector, electrification, consolidation of legislation and (unsuccessful) development of nuclear energy. Since the collapse of communism in Poland in 1989 and regaining sovereignty, free-market reforms began influencing the power sector. The culmination of these latter processes in the legal layer constituted the enactment and entry into force of the Energy Law of 1997.